Regulatory T-Cell-Mediated Suppression of Conventional T-Cells and Dendritic Cells by Different cAMP Intracellular Pathways - Rueda, Cesar M.; Jackson, Courtney M.; Chougnet, Claire A. (Frontiers in Immunology, 2016)
Regulatory T-cells (Tregs) mediate their suppressive action by acting directly on conventional T-cells (Tcons) or dendritic cells (DCs). One mechanism of Treg suppression is the increase of cyclic adenosine 3’,5’-monophosphate (cAMP) levels in target cells. Tregs utilize cAMP to control Tcon responses such as proliferation and cytokine production. Tregs also exert their suppression on DCs, diminishing DC immunogenicity by down-modulating the expression of co-stimulatory molecules and actin polymerization at the immunological synapse. The Treg-mediated usage of cAMP occurs through two major mechanisms. The first involves the Treg-mediated influx of cAMP in target cells through gap junctions. The second is the conversion of adenosine triphosphate (ATP) into adenosine by the ectonucleases CD39 and CD73 present at the surface of Tregs. Adenosine then binds to receptors on the surface of target cells, leading to increased intracellular cAMP levels in these targets. Downstream, cAMP can activate the canonical protein kinase A (PKA) pathway and the exchange protein activated by cyclic AMP (EPAC) non-canonical pathway. In this review, we discuss the most recent findings related to cAMP activation of PKA and EPAC, which are implicated in Treg homeostasis as well as the functional alterations induced by cAMP in cellular targets of Treg suppression.